Comparison of vestipitant with ondansetron for the treatment of breakthrough postoperative nausea and vomiting after failed prophylaxis with ondansetron - Kranke, P.; Thompson, J.P.; Dalby, P.L.; Eberhart, L.H.; Novikova, E.; Johnson, B.M.; Russ, S.F.; Noble, R.; Brigandi, R.A. (British journal of anaesthesia : BJA, 2015)
Postoperative nausea and vomiting (PONV) is common; ondansetron is often used as prophylaxis or for breakthrough episodes. Vestipitant is a neurokinin 1 (NK-1) receptor antagonist that is effective for prophylaxis, but its efficacy for treating established PONV is unknown. This study was performed to evaluate the efficacy and safety of vestipitant, compared with ondansetron for the treatment of breakthrough PONV in patients who had already received prophylactic ondansetron before surgery. A multicentre, randomized, single-blind (sponsor-open), parallel group study. Of 527 surgical patients, 130 (25%) had breakthrough PONV and were equally randomized to one of six i.v. doses of vestipitant (4–36 mg) or ondansetron 4 mg. The primary endpoint was the rate of patients exhibiting complete response, defined as no emesis and no further rescue medication from 10 min after infusion up to 24 h after surgery or hospital discharge. All doses of vestipitant were non-inferior to ondansetron in treating PONV after failed prophylaxis with ondansetron. However, vestipitant was superior to ondansetron in decreasing episodes of postoperative emesis and retching. The complete response rate analysis using Bayesian model averaging indicated that no vestipitant dose was superior to ondansetron. Nausea numerical rating scale scores and the times-to-PONV or discharge were similar between the vestipitant and ondansetron treatment groups. Although overall efficacy was non-inferior between vestipitant and ondansetron, the rate of emesis was lower with vestipitant. These data suggest that vestipitant may be a useful agent for the management of PONV, similar to other NK-1 antagonists. NCT01507194.